2014
DOI: 10.1111/pde.12482
|View full text |Cite
|
Sign up to set email alerts
|

Mycoplasma pneumoniae–Associated Mucocutaneous Disease in Children: Dilemmas in Classification

Abstract: There is controversy regarding precise definitions for Stevens-Johnson syndrome (SJS) and erythema multiforme (EM) major because of overlap in clinical presentations. SJS and EM major associated with Mycoplasma pneumoniae have been reported to occur in children, but Mycoplasma is more commonly reported with SJS. We sought to further characterize Mycoplasma-associated mucocutaneous disease. Through retrospective chart review over 10 years, six children hospitalized with a diagnosis of SJS who also tested positi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
11
0
3

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 13 publications
(55 reference statements)
1
11
0
3
Order By: Relevance
“…In these cases, EM tends to recur several times (9). Mycoplasma pneumoniae is also a prominent pathogen, which may also be associated with SJS (10,11). Various other aetiologies have been associated with EM (drugs, auto-immune disorders, malignancy, radiation, etc.…”
mentioning
confidence: 99%
“…In these cases, EM tends to recur several times (9). Mycoplasma pneumoniae is also a prominent pathogen, which may also be associated with SJS (10,11). Various other aetiologies have been associated with EM (drugs, auto-immune disorders, malignancy, radiation, etc.…”
mentioning
confidence: 99%
“…Hautveränderungen im Rahmen einer Infektion mit Mycoplasma pneumoniae treten häufig bei Kindern und jungen Erwachsenen im Alter zwischen 5 und 35 Jahren auf und werden meist als EM, SJS oder TEN beschrieben [1,2,4]. Während das Stevens-Johnson-Syndrom zumeist Medikamenten-assoziiert beschrieben wird, tritt das Erythema multiforme eher im Rahmen einer Infektionserkrankung auf [7].…”
Section: Diskussionunclassified
“…Beim Vollbild des SJS sind neben der Mundschleimhaut bei ¾ der Patienten das Genitale und bei ⅔ der Patienten die Augen betroffen [1]. Der Übergang zur toxischen epidermalen Nekrolyse mit großflächigen Ablösungen der Epidermis ist aufgrund der signifikant erhöhten Morbidität und Mortalität gefürchtet [7].…”
Section: Diskussionunclassified
See 1 more Smart Citation
“…Dermatological manifestations of M. pneumoniae infection vary widely from a mild erythematous maculopapular rash to severe Stevens–Johnson syndrome. Several pathogenic features of M. pneumoniae infection are attributed to immune‐mediated reactions rather than direct bacteria‐induced conditions . It has been reported that approximately 10% of patients with mycoplasma pneumonia are complicated with eosinophilia .…”
mentioning
confidence: 99%